Effectiveness of Dynamic Archive System (SIKD) in Dynamic Archival Management in Vocational School - Arinta Kusumawardhani; Irsyadul Ibad; Chairul Huda Atma Dirgatama; Is Hadri Utomo; Retno Suryawati (Economic Education Analysis Journal, 2023)
This study aims to measure the level of effectiveness of the Dynamic Archival Information System (SIKD) in managing archives. The data analysis technique used in this research is descriptive qualitative with simple tabulation calculations. Data collection techniques used interviews, literature studies and questionnaires given to 33 respondents using SIKD with 6 dimensions of the Delone and Mclean models namely system quality, information quality, service quality, use, customer satisfaction and added benefits. The results showed that the dynamic archive information system (SIKD) implemented in the School of Vocation of Universitas Sebelas Maret has been good and effective to help manage the dynamic archive. The lowest score of 2.85 is obtained in service quality dimension, because there are some types of users that can use. The 90% respondents constituting 27 letter recorders highly affect the response based on the feedback given by Structural Official user type. An in-depth interview indicates that the constraint found related to the slow response is due to human resource or the preoccupation of structural officials. Meanwhile, the overall results of the calculations show that SIKD is effective in managing official scripts in vocational schools.